Spontaneous Rupture of a Low-Grade Endometrial Stromal Sarcoma: A Case Report and Review of Imaging - Jin J; Liu Y; Cheng H (Cancer Management and Research)
Jiali Jin,1,2 Yangyang Liu,2 Haiyan Cheng1 1Department of Medical Imaging, Jincheng People’s Hospital, Jincheng, Shanxi Province, 048000, People’s Republic of China; 2Magnetic Resonance Unit, The Second Affiliated Hospital of Xinxiang Medical University, Xinxiang, Henan Province, People’s Republic of ChinaCorrespondence: Haiyan Cheng, Email 12020245@qq.comBackground: Endometrial stromal sarcoma (ESS) is a malignant tumor that develops from the mesenchymal tissue of the uterus. However, spontaneous rupture of ESS is uncommon. This case emphasizes the rarity of spontaneous rupture and the difficulties in preoperative diagnostic imaging, serving as a foundation for clinical diagnosis and prognosis.Case Description: A 52-year-old woman presented at the clinic with right lower abdominal pain, persisting for over 5 days, significantly impacting her daily activities. Self-examination revealed a palpable abdominal mass. Ultrasonography identified an inhomogeneous echogenic mass within the uterus, initially suspected to be a uterine fibroid. Subsequent magnetic resonance imaging indicated uterine fibroids with tumor rupture and bleeding. The pathological assessment confirmed low-grade ESS. The patient underwent a total hysterectomy and double adnexectomy and is now 4 months postoperative and surviving well.Conclusion: This case highlights the significance of diagnosing spontaneous rupture of ESS and emphasizes the need for increased awareness and additional research on this uncommon condition. Our results enhance comprehension of spontaneous ESS rupture and underscore the critical need for further investigation into optimal treatment approaches.Keywords: endometrial stromal sarcoma, spontaneous rupture, magnetic resonance imaging, pathology